ITTO guidelines for the restoration, management and rehabilitation of degraded and secondary tropical forests - International Tropical Timber Organization (ITTO, CIFOR, FAO, IUCN, WWF International, 2002)
This guidelines are intended to provide knowledge base on key policy, legal, institutional, ecological and silvicultural issues that need to be taken account in the planning and implementation of strategies and options for the restoration of degraded primary forests, the management of secondary forests, and the rehabilitation of degraded forest land, and they constitute an international reference standard. The guidelines are a checklist of prime objectives, principles and recommended actions. Most of the 49 principles and 160 recommended actions are relevant to all forest types in tropical countries. Annex 6 provides additional guidance on the management, restoration and rehabilitation of degraded and secondary forests in the dry tropics.